Mengayun Di Antara Liberalisme Dan Nasionalisme Pasar? Telaah Pelarangan Ekspor Biji Mentah dan Arah Politik Ekonomi Indonesia - Husnul Atiyah (Jurnal Identitas, 2023)
On January 1, 2020, the Indonesian government officially banned the export of raw nickel ore because nickel reserves are increasingly depleting as non-renewable energy. This decision caused a strong reaction and criticism from the European Union and resulted in a lawsuit against the World Trade Organization (WTO). In the context of academic discourse, this problem also raises questions about whether Indonesia’s political economy direction is moving towards market liberalism or nationalism. This is because several recent policies or regulations issued by the government could not simply tell the direction of Indonesia’s political economy ideology. Based on literature research, this paper intends to discuss the above issues in the context of international political economy. This article finds that the direction of the Indonesian economy is swinging between liberalism and economic nationalism. Looking at the ban on raw ore export shows this, but more is needed; thus, furthr study is required to suggest the political economy direction adopted by the Indonesian government.